2022
DOI: 10.3390/ijms231911261
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Loaded with Platinum Drugs for Colorectal Cancer Therapy

Abstract: Colorectal cancer is a common cancer in both men and women. Numerous studies on the therapeutic effectiveness of nanoparticles against colorectal cancer have been reported. Platinum treatments as well as other medications comprising of nanoparticles have been utilized. Drug resistance restricts the use of platinum medicines, despite their considerable efficacy against a variety of cancers. This review reports clinically licensed platinum medicines (cisplatin, carboplatin, and oxaliplatin) combined with various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 174 publications
0
6
0
Order By: Relevance
“…Although modifying the structure of the antitumor drugs is a valuable approach for the discovery of new anticancer drugs, an additional strategy to expand the pharmacological properties of compounds to improve the pharmacological effects—concomitantly leading to lower side effects—is the encapsulation of anticancer-active entities into biocompatible nanoparticles. Nowadays, several successful examples of drug encapsulation and delivery have been reported in the scientific literature [ 97 , 98 , 99 , 100 , 101 ]. On this basis, we also performed a pilot study based on the encapsulation of PTG in the core of PLGA-PEG nanoparticles, thus forming the aforementioned drug-delivery system.…”
Section: Resultsmentioning
confidence: 99%
“…Although modifying the structure of the antitumor drugs is a valuable approach for the discovery of new anticancer drugs, an additional strategy to expand the pharmacological properties of compounds to improve the pharmacological effects—concomitantly leading to lower side effects—is the encapsulation of anticancer-active entities into biocompatible nanoparticles. Nowadays, several successful examples of drug encapsulation and delivery have been reported in the scientific literature [ 97 , 98 , 99 , 100 , 101 ]. On this basis, we also performed a pilot study based on the encapsulation of PTG in the core of PLGA-PEG nanoparticles, thus forming the aforementioned drug-delivery system.…”
Section: Resultsmentioning
confidence: 99%
“…CRC cells have also developed some drug resistance to platinum agents, such as the inhibition of drug accumulation in tumor cells, as well as the acquisition of EMT. A large number of studies on drug resistance have found that exosomes loaded with miR-128-3p ( 156 ) and the application of nanoparticles ( 157 ) can re-sensitize CRC cells to platinum drugs in vivo .…”
Section: Exploration Of Neddylation As a Potential Molecularly Target...mentioning
confidence: 99%
“…With increasing cancer incidence and mortality, cancer has become a leading cause of death and poses a serious threat to the health and lives of people worldwide, making it a major global public health issue. Colorectal cancer exhibits high tumor heterogeneity and treatment typically involves a combination of surgery and chemotherapy based on disease grade, stage, and other characteristics 5 , 6 . With improvements in therapies and regimens, the 5-year survival rate of colorectal cancer patients has significantly improved to 65% 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%